2021
DOI: 10.1002/ange.202100940
|View full text |Cite
|
Sign up to set email alerts
|

Planar Hexacoordinate Carbons: Half Covalent, Half Ionic

Abstract: Herein, the first global minima containing a planar hexacoordinate carbon (phC) atom are reported. The fifteen structures belong to the CE 3 M 3 + (E = S-Te and M = Li-Cs) series and satisfy both geometric and electronic criteria to be considered as a true phC. The design strategy consisted of replacing oxygen in the D 3h CO 3 Li 3 + structure with heavy and less electronegative chalcogens, inducing a negative charge on the C atom and an attractive electrostatic interaction between C and the alkali-metal catio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…35 Recent theoretical works showed that mixed ligands and nonuniform bonding between a planar center and ligands can achieve global-minimum planar hexacoordinate species. [36][37][38][39][40][41][42] Besides isolated clusters, planar hypercoordinate motifs can also be embedded on a two-dimensional (2D) scale owing to the electronic-stabilization induced steric force and good electron delocalization. 43 Recently, a set of anti-van't Hoff and Le Bel 2D nanostructures have been found as global minima, [44][45][46][47][48][49][50][51][52][53][54][55][56] giving rise to the great possibility of potential physical and chemical applications for anti-van't Hoff and Le Bel structures.…”
Section: Introductionmentioning
confidence: 99%
“…35 Recent theoretical works showed that mixed ligands and nonuniform bonding between a planar center and ligands can achieve global-minimum planar hexacoordinate species. [36][37][38][39][40][41][42] Besides isolated clusters, planar hypercoordinate motifs can also be embedded on a two-dimensional (2D) scale owing to the electronic-stabilization induced steric force and good electron delocalization. 43 Recently, a set of anti-van't Hoff and Le Bel 2D nanostructures have been found as global minima, [44][45][46][47][48][49][50][51][52][53][54][55][56] giving rise to the great possibility of potential physical and chemical applications for anti-van't Hoff and Le Bel structures.…”
Section: Introductionmentioning
confidence: 99%
“…Though the rst planar hexacoordinate carbon (CB 6 2À with D 6h symmetry) was predicted in 2000, 23 it was conrmed to be only a local minimum, not a global minimum. 25 To date, to achieve the global-minimum planar hexacoordinate species, mixed ligands and non-uniform bonding of planar center-ligands have to be used, 26,27 and the D 6h -symmetry planar hexacoordination as a global minimum is still rare. The concept of atypical planar hypercoordination has also been extended to two-dimensional (2D) and 3D materials.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in contrast to numerous planar tetracoordinate species, only few higher coordinated species were reported so far, and mostly for planar pentacoordinate (pp) motifs. 2,3,23,24,[51][52][53][54][55][56][57][58][59][60] CAl 5 + is the first masterpiece which possesses ppC in its global minimum. 19 Readers are further referred to a recent review to know the present status of ppC systems.…”
Section: Introductionmentioning
confidence: 99%
“…2 The realization of planar hexacoordinate (ph) bonding motif, that is both thermodynamically and kinetically stable, is extremely rare. 23,24 The research in that direction was triggered by the theoretical report of CB 6 2 containing a phC 25 which was later turned out to be a high-lying isomer. 60 The first true global minimum phC was found in the D 3h symmetric CO 3 Li 3 + cluster, 24 although there is some doubt whether C-Li linkage can be called a true coordination because of electrostatic repulsion originated from the positively charged phC and Li centers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation